2012
DOI: 10.1371/journal.pbio.1001386
|View full text |Cite
|
Sign up to set email alerts
|

Smooth Muscle Tension Induces Invasive Remodeling of the Zebrafish Intestine

Abstract: Genetic analyses in zebrafish identify a novel physical signaling mechanism that drives formation of invadopodia-like structures and promotes cell invasion in vivo.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
74
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(76 citation statements)
references
References 83 publications
2
74
0
Order By: Relevance
“…For instance, the ingestive function depends also on paramecia availability (Fig. 4B), hunting success rate, and food preference among others, and the digestive function results from the synergistic action of gastric acid and pancreatic digestive enzyme secretion, peristaltic intestinal muscle contractions, epithelial nutrient absorption, and microbiota nutrient breakdown (14,27,32,41). As larval zebrafish share these features with higher vertebrates, the simultaneous experimental readout of these metrics and integration into the model represents abundant ground for future efforts.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, the ingestive function depends also on paramecia availability (Fig. 4B), hunting success rate, and food preference among others, and the digestive function results from the synergistic action of gastric acid and pancreatic digestive enzyme secretion, peristaltic intestinal muscle contractions, epithelial nutrient absorption, and microbiota nutrient breakdown (14,27,32,41). As larval zebrafish share these features with higher vertebrates, the simultaneous experimental readout of these metrics and integration into the model represents abundant ground for future efforts.…”
Section: Discussionmentioning
confidence: 99%
“…Using time-lapse imaging, the authors showed that epithelial cells have actin-rich protrusions that are enriched in cortactin and Tks5. They also observed a weak expression of MT1-MMP at the basal area of the cell (Seiler et al, 2012). Thus, cells can successfully cross the basement membrane, most likely through a combination of a proteolytic activity and mechanical forces.…”
Section: Invadosome Plasticitymentioning
confidence: 99%
“…For instance, one study has investigated the epithelial cell invasion within the developing intestine of zebrafish with a mutation in the myosin heavy chain 11 (mlt), which constitutively activates this protein, leading to a disrupted intestinal architecture (Seiler et al, 2012). Using time-lapse imaging, the authors showed that epithelial cells have actin-rich protrusions that are enriched in cortactin and Tks5.…”
Section: Invadosome Plasticitymentioning
confidence: 99%
“…60 Other studies, performed in the zebrafish, showed that intestinal epithelial cells also form invadopodia-like protrusions and invade the stroma in response to a physical signal arising from smooth muscle contractility in the larval intestine. 61 Thus, invadopodia-like protrusions are conserved subcellular structures used for BM breaching during development. Using chick embryo as a model system to study epithelial-tomesenchymal transition (EMT) in gastrulation, Nakaya and colleagues showed that destabilization of microtubules at the epiblast's basal cell cortex weaken the interactions between epiblasts and BMs, which leads to BM breakdown.…”
Section: Breaching the Bm During Developmentmentioning
confidence: 99%